Scaffold functions of 14-3-3 adaptors in B cell immunoglobulin class switch DNA recombination. - Tonika Lam (Public Library of Science (PLoS), 2013)
Class switch DNA recombination (CSR) of the immunoglobulin heavy chain (IgH) locus crucially diversifies antibody biological effector functions. CSR involves the induction of activation-induced cytidine deaminase (AID) expression and AID targeting to switch (S) regions by 14-3-3 adaptors. 14-3-3 adaptors specifically bind to 5'-AGCT-3' repeats, which make up for the core of all IgH locus S regions. They selectively target the upstream and downstream S regions that are set to undergo S-S DNA recombination. We hypothesized that 14-3-3 adaptors function as scaffolds to stabilize CSR enzymatic elements on S regions. Here we demonstrate that all seven 14-3-3β, 14-3-3ε, 14-3-3γ, 14-3-3η, 14-3-3σ, 14-3-3τ and 14-3-3ζ adaptors directly interacted with AID, PKA-Cα (catalytic subunit) and PKA-RIα (regulatory inhibitory subunit) and uracil DNA glycosylase (Ung). 14-3-3 adaptors, however, did not interact with AID C-terminal truncation mutant AIDΔ(180-198) or AIDF193A and AIDL196A point-mutants (which have been shown not to bind to S region DNA and fail to mediate CSR). 14-3-3 adaptors colocalized with AID and replication protein A (RPA) in B cells undergoing CSR. 14-3-3 and AID binding to S region DNA was disrupted by viral protein R (Vpr), an accessory protein of human immunodeficiency virus type-1 (HIV-1), which inhibited CSR without altering AID expression or germline IH-CH transcription. Accordingly, we demonstrated that 14-3-3 directly interact with Vpr, which in turn, also interact with AID, PKA-Cα and Ung. Altogether, our findings suggest that 14-3-3 adaptors play important scaffold functions and nucleate the assembly of multiple CSR factors on S regions. They also show that such assembly can be disrupted by a viral protein, thereby allowing us to hypothesize that small molecule compounds that specifically block 14-3-3 interactions with AID, PKA and/or Ung can be used to inhibit unwanted CSR.